PENENTUAN KADAR FENOLAT TOTAL DAN AKTIVITAS ANTIOKSIDAN DARI EKSTRAK DAUN DADAP MERAH (Erythrina fusca Lour) SECARA SPEKTROFOTOMETRI UV-Vis - Wardi, Epi Supri; Zulkarni R, Zulkarni R; Nurdianti, Desy (Jurnal Ilmiah As-Syifaa, 2019)
Determination of total phenolate and antioxidant activity of red leaf extract (Erythrina fusca Lour) was done by UV-Vis spectrophotometry. This study aims to determine the total phenolic content and antioxidant activity of hexane, ethyl acetate and ethanol extract. The extracts were prepared using a non-polar-maseration method with hexane, ethyl acetate and ethanol solvents. The results showed total phenolic concentration using the Folin-Ciocalteu method were 0.412 g/100 g in the hexane extract, 1.782 g/100 g in the ethyl acetate extract and 5.455 g/100 g in the ethanol extract. Antioxidant activity conducted by using FRAP method (Ferric Reducing Antioxidant Power) were obtained 0,682 mmol Fe (II)/100 g at hexane extract, 5,186 mmol Fe (II)/100 g at ethyl acetate extract and 10,591 mmol Fe (II)/100 g on the ethanol extract. The antioxidant activity of gallic acid as standard was 44.356 g mmol Fe (II)/100g.